Los conocimientos previos en la alfabetización inicial - Flores Davis, Luz Emilia (2007)
Initial alphabetization constitutes a challenge for educational systems due to its impact in the behavior of people in a literate society, as its importance for future learning of different disciplines. In this article, the role of previous knowledge is discussed for the consequent creation of significant learning areas in reading and writing. This discussion is based on the analysis of the information collected by a study on the construction processes of writing on first grade students.